Dislocation slip induced tensile plasticity and improved work-hardening capability of high-entropy metallic glass composite. (February 2022) - Liu, Minglei; Li, Wei; Lin, Shifeng; Fu, Huameng; Li, Hong; Wang, Aimin; Lin, Xiaoping; Zhang, Haifeng; Zhu, Zhengwang
Abstract: The high-entropy metallic glasses (HEMGs), combining the characteristics of high-entropy alloys (HEAs) and metallic glasses (MGs), have recently appeared and become the research focus, due to their good glass-forming ability and high strength. However, the application of HEMGs as structural material is restricted owing to the limited tensile plasticity and absence of dislocation-dominated deformation mechanism. To resolve this pressing issue, a stable β-phase HEMG composite (β-type HEMGC) Ti20 Zr20 Hf20 Nb16 Co5 Be19 composed of the bcc refractory HEA (RHEA) dendrites and the HEMG matrix was fabricated. Ti20 Zr20 Hf20 Nb16 Co5 Be19 not only exhibits good tensile ductility, but also has the improved work-hardening capability under room temperature tension. Essentially, the dislocation-dominated deformation mechanism plays a significant role in achieving the excellent combination of good tensile plasticity and improved work-hardening capability of the stable β-type HEMGC. The tensile ductility of Ti20 Zr20 Hf20 Nb16 Co5 Be19 is attributed to the dislocation-slip mechanism induced by high-stable HEA dendrites, and the dislocation pile-up phenomenon has a great influence on the improved work-hardening capability of composite. The present results provide an indepth understanding of the deformation behavior of stable β-type HEMGCs, and a reference for how to improve the strength-ductility combination of HEMG-matrix composites. Highlights: By introducing bcc high-entropy alloy (HEA) into metallic glass matrix, the mechanical properties of high-entropy metallic glass composite (HEMGC) is effectively improved. The tensile ductility of HEMGC is attributed to the dislocation-slip mechanism induced by high-stable HEA dendrites. The dislocation pile-up phenomenon significantly improves the strength and work-hardening capability of HEMGC.